1992
DOI: 10.1007/bf00123382
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies on (+)-anatoxin-a and derivatives

Abstract: Anatoxin-a (AnTX) is a highly potent agonist acting at the nicotinic acetylcholine receptor (nAChR) and represents a valuable tool in the study of this receptor. Molecular mechanics, semi-empirical and ab initio molecular orbital energy minimization procedures were conducted to investigate the conformation of AnTX. For each minimization procedure, the s-trans enone isomer of protonated AnTX was the energetically favoured conformer due to intramolecular electrostatic interactions. Our studies are discussed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Later calculations using the protonated and, given the pk A of anatoxin-a, the biologically more relevant form of anatoxina concluded that not only was the energy difference between s-cis and s-trans larger (9.4 kJ mol −1 ) but that it also favoured the s-trans conformer i.e. s-trans was more stable [ 64 ]. The message to take from this is that no truly definitive conclusions can be drawn from either set of calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Later calculations using the protonated and, given the pk A of anatoxin-a, the biologically more relevant form of anatoxina concluded that not only was the energy difference between s-cis and s-trans larger (9.4 kJ mol −1 ) but that it also favoured the s-trans conformer i.e. s-trans was more stable [ 64 ]. The message to take from this is that no truly definitive conclusions can be drawn from either set of calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they were conducted in the gas phase, ignoring possible effects arising from interactions with water. Recently, more modern computational techniques have been used to study the conformations of other nAChR ligands: ACh, epibatidene, and anatoxin-a, and it thus seemed appropriate to perform a comparable study on nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…We also considered data on the conformation of the ligand itself. Solution NMR and force-field calculations suggest that cis-and trans-chair conformations of this alkaloid are similar in energetic terms, with an approximate ratio of 3:1, and the acetyl side chain is relatively free to rotate (Thompson et al, 1992). Single-crystal X-ray diffraction analyses of an acetyl derivative (Huber, 1972) and (+)-anatoxin-a itself (Koskinen & Rapoport, 1985) show the trans-chair conformation.…”
Section: Crystallographic Analysesmentioning
confidence: 99%